2012
DOI: 10.1007/s00464-012-2237-0
|View full text |Cite
|
Sign up to set email alerts
|

The virtual reality simulator dV-Trainer® is a valid assessment tool for robotic surgical skills

Abstract: The dV-Trainer(®) simulator proves to be a valid tool to assess basic skills of robotic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 21 publications
1
94
0
3
Order By: Relevance
“…Moreover, hepatobiliary surgeons, at the beginning of their robotic learning curve, might have a limited number of simple cases that could be used as a training model. Simulation and virtual-reality surgical training are promising, but are still under development and require validation (34,35). The robotic dual console is a teaching tool that could help accelerate proficiency (36).…”
Section: Limits Of Robotic Liver Surgerymentioning
confidence: 99%
“…Moreover, hepatobiliary surgeons, at the beginning of their robotic learning curve, might have a limited number of simple cases that could be used as a training model. Simulation and virtual-reality surgical training are promising, but are still under development and require validation (34,35). The robotic dual console is a teaching tool that could help accelerate proficiency (36).…”
Section: Limits Of Robotic Liver Surgerymentioning
confidence: 99%
“…Construct validity is defined as the ability of a simulator to differentiate experts from beginners [2] . Beginners are candidates without any experience in robotic skills, whereas the term 'expert' is used in reference to a urology trainee or specialist.…”
Section: Validity Studiesmentioning
confidence: 99%
“…Another important question is if this VR system could also be used for assessment of robotic skills [22]. Recently, Perrenot et al concluded in their study that the dVT proves to be a valid tool to assess basic skills of robotic surgery on the dVSS [23].…”
Section: Discussionmentioning
confidence: 99%